2021
DOI: 10.3390/ma14051129
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Welding Current and Electrode Force on the Heat Input, Weld Diameter, and Physical and Mechanical Properties of SS316L/Ti6Al4V Dissimilar Resistance Spot Welding with Aluminum Interlayer

Abstract: Welding parameters obviously determine the joint quality during the resistance spot welding process. This study aimed to investigate the effect of welding current and electrode force on the heat input and the physical and mechanical properties of a SS316L and Ti6Al4V joint with an aluminum interlayer. The weld current values used in this study were 11, 12, and 13 kA, while the electrode force values were 3, 4, and 5 kN. Welding time and holding time remained constant at 30 cycles. The study revealed that, as t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…The permeability change curve of the ferromagnetic sample under the CMF is named conventional permeability. Therefore, the expression of permeability can be expressed by Equation (10). Equation ( 11) is obtained by differentiating the two sides of Equation (10).…”
Section: Principle Of Magneto-optical Imagingmentioning
confidence: 99%
See 2 more Smart Citations
“…The permeability change curve of the ferromagnetic sample under the CMF is named conventional permeability. Therefore, the expression of permeability can be expressed by Equation (10). Equation ( 11) is obtained by differentiating the two sides of Equation (10).…”
Section: Principle Of Magneto-optical Imagingmentioning
confidence: 99%
“…Therefore, the expression of permeability can be expressed by Equation (10). Equation ( 11) is obtained by differentiating the two sides of Equation (10). Then, according to the relationship between total differential and partial differential equation, the partial differential equation can be obtained by sorting out Equation (11), as shown in Equation (12).…”
Section: Principle Of Magneto-optical Imagingmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, depletion of chromium in adjacent zones through the consumption of secondary phase precipitations reduces corrosion resistance, particularly at high temperatures. Consuming alloying elements of base metals in area adjacent to the bonding zone reduces the alloying elements, leading to reinforcement with a solid solution and carbide deposition (such as tungsten, molybdenum, and chromium) [44][45][46][47][48][49][50][51][52][53][54][55][56][57][58]. Consequently, it is essential to apply post-bond heat treatment to remove secondary phase compounds in the diffusion-affected zones.…”
Section: Zonesmentioning
confidence: 99%
“…Reported studies have shown that if the welding current increases from 4 to 11 kA and the welding time increases from 50 to 300 ms, the diameter of the welded nugget increases [12], causing the coarse grains formation and cracks at the interface of the joint [15]. In these situations, weaker adhesion values and cracks in the weld were reported, by weakening the grain boundaries due to intermetallic compounds (Fe 2 Al 5 and Fe 4 Al 13 phases) formation [15] - [18].…”
Section: Introductionmentioning
confidence: 99%